Distribution of the exotic parasite, Lernaea cyprinacea (Copepoda, Lernaeidae) in Argentina - Plaul, Silvia Elena (2010)
Lernaea cyprinacea Linnaeus is an ectoparasitic copepod that infects the gills and skin of various freshwater fishes and amphibians tadpoles. It is capable of infecting fish at high levels, with high pathogenicity and mortality, mainly during the summer season. Besides the effects of penetration, haemorrhages and ulcerations are also caused. The objective of this study was to investigate the presence of L. cyprinacea in natural bodies of water of Argentina in the provinces of Buenos Aires, Mendoza and Río Negro; the finding of the parasite in Choele-Choel, in the province of Río Negro, is the most austral distribution of its presence. In our study, infections with L. cyprinacea showed a low host specific and they were adapted to a large variety of habitats.